Humor as an Approach Used by Teacher to Evoke Students’ Motivation in EFL Online Learning - Nashruddin Nashruddin; Fiptar Abdi Alam (JETAL: Journal of English Teaching & Applied Linguistic, 2021)
Covid-19 pandemic condition demands the learning activities to be conducted online. The current study aims to investigate the types of humor inserted by the teacher in the EFL online teaching-learning activities, and students’ responses toward the teacher’s humor. The participants of this descriptive qualitative research are an EFL teacher and 29 students of the 2nd grade at SMA Muhammadiyah Barru. To collect data about the types of humor used by the teacher, the researchers directly observe the online learning activities conducted by the teacher and his students. For gaining the deepest data about students’ responses toward the teacher’s humor, the researchers randomly interview 10 from those 29 students. The researchers found that in the online teaching-learning activities, the teacher inserted humorous words that based on the theory were classified into pun fan, joke, innuendo, malapropism, and absurdity. Besides that, the researchers also found new types of humor used by the teacher, which were then named as local humor and plesetan humor. From the interview result, it is found students’ responses towards the teacher’s humor indicate that humor maintains students’ focus in learning activities, stimulates students to solve problems quickly, and keeps students’ self-confidence in online learning.